Perancangan Apartemen Green City Bekasi dengan Pendekatan Konsep Green Building dan dengan Tema Green Nature di Kawasan Bekasi Town Square - Aguswin, Ahmad; Permana, Galih Andika; Bagastama, Arman (Universitas Pelita Bangsa, 2021)
The design of apartments must also be aware of protecting the environment. The aim of this research is to find out how necessary it is to build apartments using a green building concept approach and themed on green nature and using descriptive, documentary, comparative, and following methods. design an apartment with a green building concept so that the development of this vertical residence or apartment can solve the problem of housing needs in Bekasi City, it can accommodate many homes in a narrow area, and also by designing a green building concept the apartment also helps to protect the environment around it and can also reducing the effects of global warming, the conclusion is that the need for housing in the Kota Bekasi area is increasing, but land for housing is decreasing, therefore vertical residential development is very necessary for the Kota Bekasi area. In designing a building with a green building concept we must meet several variable requirements, namely appropriate land use, energy efficiency and conservation, water use efficiency, material resources & cycles, air quality & indoor air comfort, building environmental management.